Achieving ecological conservation impact is not enough: setting priorities based on multiple criteria. (February 2015) - Nuno, A.
<x xml:space="preserve">Abstract</x> Read the Feature Paper: Community‐based wildlife management failing to link conservation and financial viability; other Commentaries on this paper: Wildlife conservation without financial viability? The potential for payments for dispersal areas' services in Namibia and the Response from the authors: Continuous financial support will be needed